Application of Cloud-Driven Intelligent Medical Imaging Analysis in Disease Detection - Chen, Zhou; Lou, Yan; Wang, Baoming; Lei, Han; Yang, Peiyuan (Journal of Theory and Practice of Engineering Science, 2024)
The integration of cloud computing and artificial intelligence (AI) in medical imaging has revolutionized disease detection and diagnosis. This paper explores the application of cloud-driven intelligent medical imaging analysis, highlighting its ability to manage and utilize massive datasets efficiently. By leveraging the vast storage capacities, high computing power, and robust data security of cloud computing, coupled with the precision and speed of AI algorithms, medical imaging processes are significantly enhanced. The development of intelligent systems enables real-time data access, remote consultations, and mobile solutions, which improve the accessibility and availability of medical resources. This synergy not only alleviates the workload on radiologists but also supports better patient outcomes through advanced diagnostic capabilities and seamless collaboration across medical institutions. The ongoing advancements in these technologies promise to drive further innovation and enhance the quality of healthcare services.